Analysis of Rice and Paddy Commodity Distribution Chain in Banua Baru Village, Wonomulyo District - Ramadhani, Nurul Fitri; Ansyar; Adiputra Rahman (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to analyze the distribution pattern of rice commodities in Banua Baru Village. This study uses a qualitative approach with data collection techniques through observation, interviews using questionnaires, and documentation. Primary and secondary data were collected from a sample of 40 people and analyzed using descriptive percentage analysis and marketing margin analysis. The results show that there are three rice distribution patterns in Banua Baru Village, namely: (1) farmer to collector to rice mill to retailer to consumer, (2) farmer to rice mill to wholesaler to retailer to consumer, and (3) farmer to rice mill to wholesaler to consumer. This study also found that the highest marketing margin occurs in rice mills (60%), followed by collectors (12.5%), retailers (7.41%), and collectors (7.14%). Based on the value of profit margin, rice mills have the highest profit of Rp4,500/Kg, followed by collectors (Rp1,500/Kg), retailers (Rp1,000/Kg), and collectors (Rp500/Kg). This study also identifies several problems faced by farmers in marketing their rice products, such as limited information on rice prices and delayed payments by collectors.